2016
DOI: 10.5194/acp-16-8915-2016
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation efficiency of AgI: review and new insights

Abstract: Abstract. AgI is one of the best-investigated ice-nucleating substances. It has relevance for the atmosphere since it is used for glaciogenic cloud seeding. Theoretical and experimental studies over the last 60 years provide a complex picture of silver iodide as an ice-nucleating agent with conflicting and inconsistent results. This review compares experimental ice nucleation studies in order to analyze the factors that influence the ice nucleation ability of AgI. The following picture emerges from this analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 93 publications
(172 reference statements)
3
129
0
4
Order By: Relevance
“…For AgI particles the freezing efficiency in CLINCH experiments was less than in IMCA-ZINC and the onset temperature was shifted to lower values. This is further investigated in Marcolli et al (2016). For ATD, freezing efficiencies in contact and immersion mode were similar.…”
Section: Kaolinitementioning
confidence: 95%
See 1 more Smart Citation
“…For AgI particles the freezing efficiency in CLINCH experiments was less than in IMCA-ZINC and the onset temperature was shifted to lower values. This is further investigated in Marcolli et al (2016). For ATD, freezing efficiencies in contact and immersion mode were similar.…”
Section: Kaolinitementioning
confidence: 95%
“…Moreover, the freezing ability depends on the surface charge of AgI particles. A closer investigation of factors influencing the efficiency of AgI as an ice nucleus and reasons for the lower freezing efficiency in CLINCH compared with IMCA-ZINC are discussed in the companion paper by Marcolli et al (2016).…”
Section: Silver Iodidementioning
confidence: 99%
“…As a contaminant, we selected AgI particles, which are a known ice nucleation promoter. 46 To control the degree of surface contamination, we used the following procedure. For low-level contamination, we cleaned glass microscopy coverslips by treating them for 7 min with a piranha solution (1:2 solution of hydrogen peroxide in hydrochloric acid), followed by bath sonication for 1 min in acetone and 1 min in isopropyl alcohol.…”
Section: Artificial Contaminationmentioning
confidence: 99%
“…The subscripts V , L , and S take the place of parent phase (1) and daughter phase ( In order to investigate the heterogeneous condensation-desublimation nucleation transition, we examined condensation and desublimation behavior on silver iodide coated surfaces (AgI), a wellknown nucleation agent. 32 Figure 2a shows a plot of Figure 3e and f indicate the percent area fraction of the surface covered by concave pits of radius R (negative values) for our smooth and nanotextured silicon samples, respectively. Comparing the smooth and nanotextured silicon surfaces, we observed that the nanotextured surface has 18% of its area-a significant fraction-covered with nanopits with R < 10 * 12 r , while the smooth silicon has effectively none of its area covered with nanopits with R < 10 * 12 r .…”
Section: Resultsmentioning
confidence: 99%